High-content imaging of presynaptic assembly - Poon, Vivian Y.; Goh, Chiatzun; Voorhoeve, P. Mathijs; Fivaz, Marc (Frontiers in Cellular Neuroscience, 2014)
Presynaptic assembly involves the specialization of a patch of axonal membrane into a complex structure that supports synaptic vesicle exocytosis and neurotransmitter release. In mammalian neurons, presynaptic assembly is widely studied in a co-culture assay, where a synaptogenic cue expressed at the surface of a heterologous cell induces presynaptic differentiation in a contacting axon. This assay has led to the discovery of numerous synaptogenic proteins, but has not been used to probe neuronal mechanisms regulating presynaptic induction. The identification of regulatory pathways that fine-tune presynaptic assembly is hindered by the lack of adequate tools to quantitatively image this process. Here, we introduce an image-processing algorithm that identifies presynaptic clusters in mammalian co-cultures and extracts a range of synapse-specific parameters. Using this software, we assessed the intrinsic variability of this synaptic induction assay and probed the effect of eight neuronal microRNAs on presynaptic assembly. Our analysis revealed a novel role for miR-27b in augmenting the density of presynaptic clusters. Our software is applicable to a wide range of synaptic induction protocols (including spontaneous synaptogenesis observed in neuron cultures) and is a valuable tool to determine the subtle impact of disease-associated genes on presynaptic assembly.